Methodology and Applications of Remote Sensing and GIS in Environmental Mapping and Monitoring - Rai, Praveen Kumar; Mishra, Varun Narayan; Raju, K.N.P. (National Geographical Journal of India, 2022)
This review article introduces the characteristics of geography information system (GIS) and remote sensing (RS) environmental monitoring applications. The authors explicate GIS applications in ecological monitoring, water monitoring, air monitoring and environmental noise monitoring etc., then illuminate the vital role of remote sensing and GIS in environmental protection., The development and application of an integrated environmental monitoring information system will enable the sharing of information resources based on GIS and remote sensing. It will also effectively enter and analyze the spatial data and the attribute data. It will provide the information for decision-making and promote scientific analysis and decision-making in environmental protection. Remote Sensing and GIS applications in environmental monitoring are ascendant and its application in information management of environmental monitoring will bound to the cause of environmental protection to a new historical process